2004
DOI: 10.1080/02791072.2004.10400032
|View full text |Cite
|
Sign up to set email alerts
|

Crack Cocaine and Sex

Abstract: The impact of crack cocaine use on number of sex partners was examined using bivariate analyses and a logistic model on a national treatment cohort of 4939 individuals. Number of sex partners over the last 12 months was dichotomized as none/one versus multiple partners for the logistic analyses. The model included 11 independent variables not including prostitution or use of crack cocaine. For both genders, the bivariate analyses showed significant positive associations between crack use and number of partners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 10 publications
0
20
0
4
Order By: Relevance
“…[16][17] The most frequent risk behaviours in this population are having a high number of sexual partners and engaging in unprotected sex, usually motivated by the need to acquire the substance. [36][37] In the present study, we did not investigate such risky behaviour. Therefore, prior use of intravenous drugs was considered the main cause for HIV infection among these users.…”
Section: -12mentioning
confidence: 99%
“…[16][17] The most frequent risk behaviours in this population are having a high number of sexual partners and engaging in unprotected sex, usually motivated by the need to acquire the substance. [36][37] In the present study, we did not investigate such risky behaviour. Therefore, prior use of intravenous drugs was considered the main cause for HIV infection among these users.…”
Section: -12mentioning
confidence: 99%
“…In the United States, female prostitution has already been extensively reported and male prostitution has recently been identifi ed. 12, 15 Maranda et al 15 suggested that there were different etiologies for the two types of prostitution. That is, while female prostitution was exclusively the product of the craving for crack, male prostitution seemed to be the combined product of the craving and the increased sexual libido induced by crack.…”
Section: Illegal Activitiesmentioning
confidence: 99%
“…12, 15 Maranda et al 15 suggested that there were different etiologies for the two types of prostitution. That is, while female prostitution was exclusively the product of the craving for crack, male prostitution seemed to be the combined product of the craving and the increased sexual libido induced by crack.…”
Section: Illegal Activitiesmentioning
confidence: 99%